Previously unrecognized risk factors for severe hypoglycaemia requiring emergency medical care in insulin‐treated type 2 diabetes: Results from a real‐world nested case‐control study. Issue 7 (11th April 2022) - Settles, Julie; Kan, Hong; Child, Christopher J.; Gorritz, Magdaliz; Multani, Jasjit K.; McGuiness, Catherine B.; Wade, Rolin L.; Frier, Brian M.
Abstract: Aim: Several risk factors for severe hypoglycaemia (SH) are associated with insulin‐treated diabetes. This study explored potential risk factors in adults with insulin‐treated type 2 diabetes mellitus (T2DM). Materials and Methods: In this case‐control study, adults with T2DM initiating insulin were identified in the IQVIA PharMetrics® Plus database. The index date was the date of the first SH event (cases). Using incidence‐density sampling, controls were selected from those who had been exposed 'at risk' of SH for the same amount of time as each case. After exact‐matching on the well‐established factors, previously unreported risk factors were evaluated through conditional logistic regression. Results: In 3153 case‐control pairs, pregnancy [odds ratios (OR) = 3.20, p  = .0003], alcohol abuse (OR = 2.43, p  < .0001), short‐/rapid‐acting insulin (OR = 2.22/1.47, p  < .0001), cancer (OR = 1.87, p  < .0001), dementia/Alzheimer′s disease (OR = 1.73, p  = .0175), peripheral vascular disease (OR = 1.59, p  < .0001), antipsychotics (OR = 1.59; p  = .0059), anxiolytics (OR = 1.51, p  = .0012), paralysis/hemiplegia/paraplegia (OR = 1.51, p  = .0416), hepatitis (OR = 1.50, p  = .0303), congestive heart failure (OR = 1.47, p  = .0002), adrenergic‐corticosteroid combinations (OR = 1.45, p  = .0165), β‐adrenoceptor agonists (OR = 1.40, p  = .0225), opioids (OR = 1.38, p  < .0001), corticosteroids (OR = 1.35, p  = .0159), cardiac arrhythmia (OR = 1.29. p  = .0065), smoking (OR = 1.28, p  = .005), Charlson Comorbidity Index score 2 (OR = 1.28, p  = .0026), 3 (OR = 1.41, p  = .0016) or ≥4 (OR = 1.57, p  = .0002), liver/gallbladder/pancreatic disease (OR = 1.26, p  = .0182) and hypertension (OR = 1.19, p  = .0164) were independently associated with SH. Conclusions: Although all people with insulin‐treated diabetes are at risk of SH, these results have identified some previously unrecognized risk factors and sub‐groups of insulin‐treated adults with T2DM at greater risk. Scrutiny of current therapies and comorbidities are advised as well as additional glucose monitoring and education, when identifying and managing SH in vulnerable populations.